Health and physical education as an important part of school curricula: a comparison of schools for the deaf in the Czech Republic and the United States - Kurková, Petra; Scheetz, Nanci A; Stelzer, Jiří (American annals of the deaf, 2010)
The authors describe and compare how physical education classes and healthy lifestyle concepts are taught in selected Czech and U.S. schools for the deaf. Professionals who participated in the study included principals and teachers employed by 4 schools for the deaf. Data from schools were collected during the summer and fall semesters, and subsequent interviews were conducted with the principals and physical education teachers. Unique characteristics were exhibited by each of the 4 schools. The settings for extracurricular physical and sports activities varied by school type (residential or nonresidential). Findings indicated that the general trend in physical education has changed from a focus on sports performance to health-promoting activities. There were opportunities for teachers to revise curriculum programs to further promote the health and academic success of students who are deaf or hard of hearing.
Keywords: hluchota; Students; průzkumy a dotazníky; Persons with Hearing Disabilities; Health Education; Education of Persons with Hearing Disabilities; Surveys and Questionnaires; Life Style; životní styl; Physical Education and Training; lidé; Deafness; cvičení; rehabilitace sluchově postižených; sluchově postižení; Curriculum; dieta; výuka sluchově postižených; Humans; zdravé chování; Spojené státy americké; Diet; Czech Republic; Health Knowledge, Attitudes, Practice; zdraví - znalosti, postoje, praxe; United States; Health Behavior; Česká republika; kurikulum; studenti; Correction of Hearing Impairment; Exercise; tělesná výchova; zdravotní výchova